Dynamic modeling of semitrailer trucks equipped by steered wheels - Diachuk, M.; Lykhodii, O.; Leontiev, D.; Ryzhykh, L.; Aleksandrov, Y. V.; Александров, Ю. В.; ORCID: http://orcid.org/0000-0002-5871-8344 (Journal of Mechanical Engineering and Sciences. – 2022. – № 16 (1) . – Р. 8691–8705, 2022)
У статті пропонується загальний підхід до створення комплексної розрахункової моделі, яка встановлює зв'язок між динамікою руху автопоїзда та активними системами керування напівпричепом. Ключовим моментом є розроблена математична модель на основі матричної методики, що дозволяє створювати універсальну імітаційну модель серед Simulink. Створений метод із рекомендованим програмним продуктом дозволив підвищити точність моделювання криволінійного шляху автопоїзда на 10% при зменшенні часу на розрахунок приблизно на 50% порівняно з класичним методом. За рахунок експериментальних досліджень підтверджено адекватність запропонованої імітаційної моделі динаміки руху автопоїзда, загальна відносна похибка порівняно з теоретичними дослідженнями становила не більше 5%. Додаткове об'єднання з шасі напівпричепа активної системи керування поворотом зменшує лінійну величину постійного руху автопоїзда по колу на 14,5% порівняно з напівпричепом без цієї системи, що також є позитивним для забезпечення маневреності автопоїзда.

Improving the performance of articulated vehicles is not only by completing the tractor systems, but also by intellectualizing the trailer links (TL), is a complex task. In this regard, the search for and justification of the implementation of controlled TL systems is an important process (Intelligent Trailer). The research has been carried for the purpose of development of the systemic approach from the idea schematization to the practical recommendations. The paper proposes a general approach for creating a comprehensive calculation model that establishes a link between the dynamics of movement of articulated vehicle and the active controlling systems of the semitrailer. The key moments is the developed mathematical model based on matrix technique that facilitates the creation of the universal simulation model in the Simulink environment. The created method with recommended programming product afforded to increase the exactness of modelling of curving way of articulated vehicle on 10 % under the diminishing of time on the calculation about 50 % in comparison with classical method. At the expense of experimental investigation there was confirmed appropriateness of proposed imitation model of movement dynamics of articulated vehicle, general relative mistake in comparison with theoretical investigations was not over than 5%. Additional combining to semitrailer chassis the active turning control system diminishes the size line of constant movement of articulated vehicle in the circle on 14,5% in comparison with semitrailer without this system, which is also positive from the point of safety of articulated vehicle maneuverability.

Улучшение характеристик сочлененных транспортных средств не только за счет комплектации систем тягача, но и за счет интеллектуализации прицепных звеньев (ТС) является сложной задачей. В связи с этим важным процессом является поиск и обоснование реализации управляемых систем TL (IntelligentTrailer). Исследование проведено с целью развития системного подхода от схематизации идеи до практических рекомендаций. В статье предлагается общий подход к созданию комплексной расчетной модели, устанавливающей связь между динамикой движения автопоезда и активными системами управления полуприцепом. Ключевым моментом является разработанная математическая модель на основе матричной методики, позволяющая создавать универсальную имитационную модель в среде Simulink. Созданный метод с рекомендованным программным продуктом позволил повысить точность моделирования криволинейного пути автопоезда на 10 % при уменьшении времени на расчет примерно на 50 % по сравнению с классическим методом. За счет экспериментальных исследований подтверждена адекватность предложенной имитационной модели динамики движения автопоезда, общая относительная погрешность по сравнению с теоретическими исследованиями составила не более 5 %. Дополнительное объединение с шасси полуприцепа активной системы управления поворотом уменьшает линейную величину постоянного движения автопоезда по кругу на 14,5% по сравнению с полуприцепом без этой системы, что также является положительным с точки зрения обеспечения маневренности автопоезда.
Diachuk, M. Dynamic modeling of semitrailer trucks equipped by steered wheels / M. Diachuk, O. Lykhodii, D. Leontiev, L. Ryzhykh, Yu. Aleksandrov // Journal of Mechanical Engineering and Sciences. – 2022. – № 16 (1) . – Р. 8691–8705. – DOI: https://doi.org/10.15282/jmes.16.1.2022.04.0687.
Diachuk, O. Lykhodii, Leontiev, D., L. Ryzhykh, & Yu. Aleksandrov. (2022). Dynamic modeling of semitrailer trucks equipped by steered wheels. Journal of Mechanical Engineering and Sciences, 16(1), 8691–8705. https://doi.org/10.15282/jmes.16.1.2022.04.0687.
Keywords: електронне управління; керовані колеса причепа; Simulink-модель; динаміка автомобіля; напівпричепи; система рульового керування; steer-by-wire; trailer's steered wheels; Simulink-model; vehicle dynamics; semitrailer trucks; steering system; электронное управление; управляемые колеса прицепа; динамика автомобиля; полуприцепы; система рулевого управления; Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u WoS